Ex-situ catalytic microwave-assisted gasification of sewage sludge over Ni-modified MIL-100 (Fe) derived catalysts: Tar reforming for hydrogen-rich syngas - Mingtao Hu; Huiwen Wu; Wenyi Deng; Lingyu Tai; Xuerong Zheng; Weihao Li; Yaxin Su; Run Xu (Journal of Environmental Chemical Engineering, 2026)

Chlorine transformation during iron ore sintering co-processing of MSWI fly ash: Phase evolution, metal coupling, and risk-relevant environmental stability - Run Shi; Hao Wang; Congqi Zhang; Rongrong Lei; Hongzhi Ma; Yi Xing; Wei Su; Tingshuang Leng; Yulan Liang (Journal of Hazardous Materials, 2026)

Experimental and numerical investigation into the interfacial performance of Fe-SMA strips bonded to cold-formed steel C-section substrates - Hai-Tao Wang; Wen Su; Han-Ying Qi; Zhiqiang Dong; Xinliang Sun; Run-Ze Zhu (Engineering Structures, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Impacts of extreme drought events on forest ecosystem resilience in mainland Southeast Asia - Lusha Ma; Kun Yang; Zongqi Peng; Run Sun; Mingfeng Zhang; Danni Su; Jingcong Ma; Yanhui Zhu; Xianchun Pan (Science Bulletin, 2026)

Coordinated EISCAT and all-sky imager observations of dayside aurora effects on polar cap patch vertical properties - Zhiwei Wang; Desheng Han; Huixuan Qiu; Yong Wang; Huigen Yang; Jian Zhang; Jianjun Liu; Xiangcai Chen; Qiang Zhang; Su Zhou; Run Shi (Science China Earth Sciences, 2026)

Research progress on co-processing of MSWI FA using high-temperature industrial waste heat - Hongzhi Ma; Congqi Zhang; Hao Wang; Run Shi; Hao Li; Yan Zhang; Xuguang Wang; Wei Su; Yi Xing; Lei Zheng (Process Safety and Environmental Protection, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

A unified intracellular pH landscape with SITE-pHorin: a quantum-entanglement-enhanced pH probe - Shu-Ang Li; Xiao-Yan Meng; Su Zhang; Ying-Jie Zhang; Run-Zhou Yang; Dian-Dian Wang; Yang Yang; Pei-Pei Liu; Jian-Sheng Kang (Science China Life Sciences, 2026)

Soil cadmium and pyrene drive earthworm burrowing inhibition and modify mucus characteristics: Toward non-destructive biomarkers - Weipeng Wang; XiaoSa Wang; Run Su; Qian Xu; Congying Wang; Yonghua Zhao; Zhiming Shi (Journal of Hazardous Materials, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

Urban-industrial synergies in Sustainability: Evaluating the Co-processing of MSWI fly ash in industrial kilns from environmental and economic perspectives - Run Shi; Fan Fei; Xuguang Wang; Dawei Liu; Shuang Wu; Junwei Bai; Yan Zhang; Wei Su; Rongrong Lei; Hao Wang; Hongzhi Ma (Journal of Cleaner Production, 2025)

Effects of periodic starvation on the characteristics and microbial communities of anammox sludge - Yufeng Zheng; Liangliang Shi; Run Su; Wenhui Min; Yan Wei; Bin Ma (Journal of Environmental Chemical Engineering, 2025)

Restoration of secondary forest in the Greater Mekong Subregion struggles to offset primary forest carbon losses - Zongqi Peng; Yanhui Zhu; Kun Yang; Yi Luo; Xixi Lu; Jiasheng Wang; Yang Zhang; Danni Su; Run Sun; Mingfeng Zhang; Jingcong Ma; Yang Liu; et al. (Global and Planetary Change, 2025)

Comammox and AOA responses to ammonia loading rate in oligotrophic environments - Run Su; Litong Shi; Yan Wei; Bin Ma (Water Research, 2025)

Centrifuge model study of vertical ultimate bearing capacity of pile foundations in overconsolidated clay - Run Liu; Yu Jiang; Chengfeng Li; Guangsi Chen; Chunyang Su; Xiaoyu Long (Ocean Engineering, 2025)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Study on the thermo-hydraulic behaviors within a CiADS 61-pin wire-wrapped fuel assembly under porous blockage conditions based on LBEblockageFoam - Yun-Xiang Li; Run-Sheng Yang; Yue Li; Xing-Kang Su; Yi-Wen Han; Zi-Nan Huang; Lu Meng; Song Li; You-Peng Zhang; Lu Zhang; Wei Jiang (Annals of Nuclear Energy, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Cadmium and pyrene in the soil modify the properties of earthworm-mediated soil - Zhiming Shi; Jie Yan; Run Su; Shuyu Shi; Wenwen Li; Yonghua Zhao; Juan Zhang; Congying Wang (Science of The Total Environment, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

A novel stress concentration inspection method for marine oil and gas pipeline based on UNSM - Jiaxing Xin; Jinzhong Chen; Renyang He; Rui Li; Xiaolong Li; Chang Liu; Run-kun Lu; Zhengda Su; Wenbo Han (Ocean Engineering, 2024)

Phosphorus recovery from synthetic anaerobic fermentation supernatant via vivianite crystallization: Coupling effects of various physicochemical process parameters - Jia-Shun Cao; Su-Na Wang; Run-Ze Xu; Jing-Yang Luo; Bing-Jie Ni; Fang Fang (Science of The Total Environment, 2023)

A predictive model for determining the nitrite concentration in the effluent of an anammox reactor using ensemble regression tree algorithm - Yikun Huang; Run Su; Yinan Bu; Bin Ma (Chemosphere, 2023)

Methyl-functionalized Zn-MOF for selective adsorption and separation of acetylene - Zi-Han Wang; Run-Han Su; Gang-Ding Wang; Wen-Juan Shi; Lei Hou (Journal of Environmental Chemical Engineering, 2023)

Bed level changes in the surf zone during post-storm beach recovery - Pengpeng Hu; Zhiqiang Li; Chunhua Zeng; Daoheng Zhu; Run Liu; Qianxin Su; Jieping Tang; Yamin Zhu (Frontiers in Marine Science, 2023)
The study of post-storm beach recovery is important for economic development and the protection of life in coastal areas. In this study, field observations were conducted for 21 days in the surf zone of Dongdao Beach, Hailing Island, China, after tropical storm “Cempaka”. Data on depth, wave, Eulerian velocity, sediment, three-dimensional topography of the beach, and high-frequency variations in bed-level elevation were collected. The results showed that the beach experienced medium- to low- to medium-energy waves during field observations and covered two complete astronomical tide cycles. Contrary to the effect of wave energy conditions on beaches under normal wave conditions, a higher wave energy during beach recovery can promote silting and accelerate beach recovery. Tidal water level is an important factor affecting beach restoration, and a smaller tidal range is conducive to beach accretion. In a mixed semidiurnal tide, beach erosion and accretion occurred in the “highest tide” and “sub-highest tide” tidal cycles, respectively, and the combined effect of the two affected the change in the bed level in a mixed semidiurnal tide. After the storm, the hydrodynamic forcing mechanism and self-organization process of the sand bar jointly drove the formation of the topography of the bar channel in the surf zone. After the storm stopped, the spectral energy in free surface elevation was mainly distributed in the very low frequency and decayed rapidly at the infragravity band. The very low-frequency pulsation of the surf zone during recovery is a prominent feature of bed-level elevation, depth, and velocity. This study provides a good case for the study of hydrodynamic and bed level changes in the post-storm surf zone, as well as a reference for future studies of the intrinsic mechanisms post-storm beach recovery processes around the world.

A novel method for immobilizing anammox bacteria in polyurethane foam carriers through dewatering - Yufeng Zheng; Yuying Zhao; Run Su; Ni An; Youliang Zhang; Yan Wei; Bin Ma (Journal of Water Process Engineering, 2023)

A crack characterization model for subsea pipeline based on spatial magnetic signals features - Jiaxing Xin; Rui Li; Jinzhong Chen; Run-kun Lu; Chang Liu; Zhengda Su; Renyang He; Hongwu Zhu (Ocean Engineering, 2023)

Landslide mapping and analysis along the China-Pakistan Karakoram Highway based on SBAS-InSAR detection in 2017 - Xiao-jun Su; Yi Zhang; Xing-min Meng; Dong-xia Yue; Jin-hui Ma; Fu-yun Guo; Zi-qiang Zhou; Mohib Ur Rehman; Zainab Khalid; Guan Chen; Run-qiang Zeng; Fu-meng Zhao (Journal of Mountain Science, 2021)

Analysis of future drought characteristics in China using the regional climate model CCLM - Jinlong Huang; Jianqing Zhai; Tong Jiang; Yanjun Wang; Xiucang Li; Run Wang; Ming Xiong; Buda Su; Thomas Fischer (Climate Dynamics, 2018)

Population structure and diversity of citrus tristeza virus (CTV) isolates in Hunan province, China - Cui Xiao; Run-Xian Yao; Fang Li; Su-Ming Dai; Grazia Licciardello; Antonino Catara; Alessandra Gentile; Zi-Niu Deng (Archives of Virology, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Spatiotemporal distributions of influential tropical cyclones and associated economic losses in China in 1984–2015 - Yanjun Wang; Shanshan Wen; Xiucang Li; Fischer Thomas; Buda Su; Run Wang; Tong Jiang (Natural Hazards, 2016)

A convenient four-component one-pot synthesis of 2-amino-1,3,4-thiadiazoles in water - Peng Liu; Ao-Ze Su; Yuan-Qiang Wang; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2014)

Pretreatment of PC12 Cells with 17β-estradiol Prevents Aβ-Induced Down-Regulation of CREB Phosphorylation and Prolongs Inhibition of GSK-3β - Yanxing Chen; Ying Su; Xiaoqin Run; Zhou Sun; Tao Wang; Shenggang Sun; Zhihou Liang (Journal of Molecular Neuroscience, 2013)

Effect of Zinc Source on Performance, Zinc Status, Immune Response, and Rumen Fermentation of Lactating Cows - Run L. Wang; Jian G. Liang; Lin Lu; Li Y. Zhang; Su F. Li; Xu G. Luo (Biological Trace Element Research, 2013)